ANALYSIS OF MEDICINAL PROPERTIES OF VIGNA ACONITIFOLIA (MATKI) - PANICKER, SUNEETA; HAMDULE, ANAM (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The seeds and sprouts of matki bean (Vigna aconitifolia), a common food, contain abundant nutrients with biological activities. This work was focused to analyze and compare the medicinal properties of seeds and sprouts of matki beans, with the goal of providing scientific evidence for better application of this commonly used food as a medicine. Methods: Using Soxhlet apparatus, ethanol extracts of matki bean sprouts and seeds were prepared. Anti-inflammatory activity (inhibition of protein denaturation, inhibition of heat induced hemolysis, and inhibition of protease activity), antioxidant activity, and antihypertensive activity were determined for both sprout and seed extracts. Results: The anti-inflammatory activity of sprout ethanol extract was found to be highest. Sprout ethanol extract inhibited the activity angiotensin-I-converting enzyme (ACE1) which was maximum as compared to seed extracts. Same was observed for the antioxidant activity, sprout ethanol extract showed higher activity than the seed extract. Conclusion: The results of the present study will help us to use Vigna aconitifolia as a healthy herbal alternative for the existing chemical remedies for various disorders and rule out the issue of side effects and resistance.